Empresa Metalúrgica da Longra, um caso no modo português de industrialização : estudo sob os regimes de acção - Lage, Maria Otília Pereira (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
This paper continues our research study entitled Metalúrgica da Longra (1920- 1993): ancoragem para um estudo sob os regimes de acção. It is an historical and social case study treading the line between tradition and innovation, based in the sociology of action and centred in a composite analysis of diverse elements: collective spaces and factory objects, activities and interrelations, paths and strategies of the actors/actants from this emblematic company, seen here as manifestations of compromise/dispute and plans of action, as points of view or as “worlds”.